Relationship between the Use of Video-Based Learning Media and Digital Literacy with Students’ Learning Motivation - Pranciska Gamilina; Muhammad Noor (MANAZHIM, 2026)
Although technology-enhanced learning has received considerable scholarly attention, quantitative empirical evidence on the concurrent relationships among video-based learning media, digital literacy, and learning motivation among elementary school students remains limited. This study aimed to analyze the relationships between video-based learning media and digital literacy with students’ learning motivation, both separately and simultaneously. A quantitative correlational design was employed at SDN Sungai Raya 1 from April to June 2026. Using total sampling, the study involved 63 students in Grades IV–VI. Primary data were collected using a four-point Likert-scale questionnaire and analyzed through Pearson correlation, multiple regression, and partial correlation analyses. The findings showed that video-based learning media had a positive and significant relationship with learning motivation (r = 0.654, p < 0.05), while digital literacy was also positively and significantly associated with learning motivation (r = 0.522, p < 0.05). Simultaneously, video-based learning media and digital literacy explained 46.3% of the variance in learning motivation (R² = 0.463, p < 0.05). Partial correlation analysis further confirmed that each independent variable contributed to learning motivation after controlling for the other variable. The study concludes that the integration of engaging video-based learning media and the strengthening of students’ digital literacy are important factors in enhancing learning motivation in elementary education. These findings contribute to the literature on technology-enhanced learning and offer practical implications for teachers and schools in designing motivating, digitally supported learning environments.